Anesthesia Management for Evacuation of Cerebral Abscess in Geriatric Patient with Myasthenia Gravis - Suarjaya, I Putu Pramana; Purwanto, Osmond; Wundiawan, Kristian Felix; J. Sutawan, Ida Bagus Krisna (Jurnal Neuroanestesi Indonesia, 2024)
A Cerebral abscess is an intracranial focal abscess which is a life-threatening emergency. Myasthenia gravis is an autoimmune disorder caused by antibodies targeting the neuromuscular junctions post-synaptic receptor. A seventy-three-year-old male, with an intra-axial tumor in the frontoparietal region underwent craniotomy for abscess evacuation. The Patient also has a history of hypertension and myasthenia gravis under treatment of dexamethasone and pyridostigmine. Anesthesia induction was performed with thiopental, opioid analgesics with fentanyl, neuromuscular blocking agent (NMBA) with rocuronium, and scalp block. The Patients depth of neuromuscular block was monitored with a Train-of-Four (TOF). Surgery was performed in a supine position, duration of surgery was 4.5 hours. The Patient was extubated in the operating theatre, monitored in the intensive care unit, and discharged home on the nineteenth day. Anesthetic management in geriatric patients with cerebral abscesses accompanied by myasthenia gravis has become complex due to the interaction of disease state, medical treatment, anesthetic drugs especially neuromuscular blocking agents, and surgical stress. The Patient was at risk for residual paralysis and had high sensitivity to nondepolarizing neuromuscular blocking agents, so the use of train-of-four (TOF) was very helpful for extubating this patient safely.